The External Exposome and Allergies: From the Perspective of the Epithelial Barrier Hypothesis - Celebi Sozener, Zeynep; Özbey Yücel, Ümüs; Altiner, Seda; Ozdel Oztürk, Betül; Cerci, Pamir; Türk, Murat; Gorgülü Akin, Begüm; Akdis, Mübeccel; Yilmaz, Insu; Ozdemir, Cevdet; Mungan, Dilsad; Akdis, Cezmi A. (Frontiers in Allergy, 2022)
In the last decades, we have seen a rapid increase in the prevalence of allergic diseases such as asthma, allergic rhinitis, atopic dermatitis, and food allergy. It has become apparent that genetic predisposition cannot solely explain this recent phenomenon. There has been a concomitant increase in the prevalence of allergic diseases with exposure to chemicals in our daily life, without sufficient safety regulations and control. The environmental changes caused by modernization not only impact human health but the entire ecosystem. Exposure to altered environmental factors such as increased pollution, microplastics, nanoparticles, tobacco smoke, food emulsifiers, detergents, and household cleaners, climate change, loss and change in microbial biodiversity and modifications in dietary habits may disrupt the epithelial barriers of the skin, respiratory and gastrointestinal tracts making us more vulnerable to exogeneous allergens and microbes. The collection of factors that we are exposed to during our lifetime is known as the external exposome. Herein, the impact of changes in the external exposome observed during the last decades on the epithelial barriers, and its association with the development of allergic diseases is reviewed in support of the recently proposed epithelial barrier hypothesis.